Análise de cenários com redução da demanda da orizcultura na bacia do rio Santa Maria com aplicação do modelo cruz - Cunha, Christhian Santana (2014)
The demand for water in the various sectors of society is increasing due to factors such as population growth, expansion of agricultural land, depletion of water resources and water quality decreased. Among these uses these demands arise that there are two groups of water, consumptive and non-consumptive. Consumptive uses are characterized by causing a change in the quantity or quality of water, either through funding or evictions. Non-consumptive uses do not cause significant changes in the quantity and quality of water, but depend on these to be realized. The irrigation of rice is a consumptive use that is considered high pollution impact by demanding too much water in their production process. The Rio Grande do Sul is responsible for approximately 65% of rice production in Brazil. The watershed of the river Santa Maria, is characterized by having focused their economic bases for rice cultivation and livestock. In the past there have been conflicts over water use between sectors of users of the basin (water supply and irrigation). Thus, this paper proposes the creation of scenarios with the gradual reduction in a range of 1% to 15% in the demand of water for irrigation of rice in funding of water held in the rivers in BHRSM. With the aim of analyzing the results proposed to the management of water demand can assist and serve as input for the process of water resources management. Initially 5 scenarios, Scenario 0, which characterizes the present moment basin, Scenario 1, 2, 3 and 4 which have as a methodological proposal to reduce the demand for water for irrigation were built. The results obtained in this work allow us to analyze the management of water demand can help to increase water availability. The scenarios simulated for the months from November to February showed the highest percentage of attendance when compared to current demand. However, the month of January still has some hydrological drought in reference sections, being necessary to think about rationing or the use of available water in existing reservoirs in the basin. It is estimated that the results obtained with the simulation in demand management, can support the management of water resources of the basin.